Electromyographic analysis of the lower limb muscles in low- and high-handicap golfers - Marta, S.; Silva, L.; Vaz, J. R.; Castro, M. A.; Reinaldo, G.; Pezarat-Correia, P. (Research Quarterly for Exercise and Sport, 2016)
Purpose: The aim of this study was to compare the electromyographic patterns of the lower limb muscles during a golf swing performed by low- and high-handicap golfers. Method: Ten golfers (5 low- and 5 high-handicap) performed 8 swings using a 7-iron. Surface electromyography (EMG) was recorded for the following lower limb muscles on both sides: biceps femoris, semitendinosus, gluteus maximus, vastus medialis and lateralis, rectus femoris, tibialis anterior, peroneus longus, and gastrocnemius medialis and lateralis. The golf-swing phases were determined by 3-dimensional high-speed video analysis. Results: Compared with the high-handicap golfers, the low-handicap golfers performed the forward swing with a shorter duration of the swing phases, with the exception of the late follow-through, where they exhibited longer duration. Considering the EMG patterns, the low-handicap golfers showed a tendency for the studied muscles to reach an activation peak earlier and presented statistically significant higher muscle activity in some of the lower limb muscles, mainly from the left side. Conclusion: Differences between low- and high-handicap golfers were found in the average duration of swing phases and in the activation level of the lower limbs, with more evidence on muscles from the left side.